2020
DOI: 10.1213/ane.0000000000004402
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine Activates Multiple Proapoptotic and Inflammatory Signaling Pathways That Might Subsume to Trigger Epidural-Related Maternal Fever

Abstract: BACKGROUND: Epidural-related maternal fever (ERMF) is an adverse effect of epidural analgesia during labor and is associated with perinatal and neonatal morbidity. Local anesthetics have been proposed to trigger ERMF via sterile inflammation. Ropivacaine is currently the most frequently used epidural anesthetic and considered least toxic. This study investigates molecular effects of ropivacaine on human umbilical vein endothelial cells (HUVECs) as model system for endothelial cells and human placen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…13 The immunomodulation mechanism is that the local anaesthetic either stimulates the release of interleukin-6, and thus induces activity in the pro-pyrogenic inflammatory pathway or inhibits the release of interleukin-1 receptor antagonist, and thus reduces the activity in the anti-pyrogenic inflammatory pathway, or both. 14,15 Although not a primary focus, this systematic review found no evidence favouring one mechanism.…”
Section: Study Question 1: Epidural Analgesia and Intrapartum Hyperthermiamentioning
confidence: 65%
See 1 more Smart Citation
“…13 The immunomodulation mechanism is that the local anaesthetic either stimulates the release of interleukin-6, and thus induces activity in the pro-pyrogenic inflammatory pathway or inhibits the release of interleukin-1 receptor antagonist, and thus reduces the activity in the anti-pyrogenic inflammatory pathway, or both. 14,15 Although not a primary focus, this systematic review found no evidence favouring one mechanism.…”
Section: Study Question 1: Epidural Analgesia and Intrapartum Hyperthermiamentioning
confidence: 65%
“…However, the proposed immunomodulation mechanism of epidural hyperthermia may link with the cytokine hypothesis. 14,15 The diagnosis of clinical chorioamnionitis requires intrapartum hyperthermia in addition to other clinical signs of infection, such as tachycardia (maternal and fetal), tachypnoea, leucocytosis, and foul-smelling vaginal discharge. 96 However, of these symptoms, only foul-smelling vaginal discharge cannot be attributed to the hyperthermia itself.…”
Section: Study Question 2: Intrapartum Hyperthermia and Neonatal Brain Injurymentioning
confidence: 99%
“…While the exact pathophysiological mechanism is not well understood, existing evidence suggests that epidural-related maternal fever may reflect a non-infectious inflammatory process [ 27 ]. A recent lab-based study conducted by Wohlrab et al [ 28 ] showed that ropivacaine may induce the release of IL-6 and IL-8 cytokines and activate multiple proapoptotic and inflammatory signalling pathways (caspase, NFKB, and P38), triggering epidural-related maternal fever. Despite this, EA appeared to have no impact on assisted vaginal delivery rates and the duration of the first and second stages of labour in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The one with the strongest evidence is that local anesthetics either release proinflammatory cytokines or inhibit anti‐inflammatory cytokines that affect endothelial, trophoblastic, and white blood cells 10–12 . A recent laboratory study showed a ropivacaine‐induced apoptosis and inflammatory cytokines in umbilical cord tissue 13 . Another theory is that epidural analgesia blocks a sympathetic response, decreasing sweating and hyperventilation and, therefore, lowering ability to dissipate heat.…”
Section: Should Midwives Care That Epidural Analgesia Causes Maternal Intrapartum Fever?mentioning
confidence: 99%